Proceedings 39th International Conference and Exhibition on Technology of Object-Oriented Languages and Systems. TOOLS 39
DOI: 10.1109/tools.2001.941655
|View full text |Cite
|
Sign up to set email alerts
|

The .NET Contract Wizard: adding Design by Contract to languages other than Eiffel

Abstract: Reliabiliiy is a key concern in the current state of sofmare industry. Producing software without defects is still very difJicult. Therefore it is crucial to benefit from high-level language mechanisms such as assertions. Nevertheless contracts are mostly a specificity of the Eiffel language. This observation convinced ISE to build a new product, the Contract Wizard, which aims at providing .NET developers with the abiliiy to add contracts to a .NET assembly independently from the .NET language it was initiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 1 publication
0
11
0
2
Order By: Relevance
“…Besides the ones mentioned above there are numerous other runtime assertion checking facilities that have been developed. Here are some that are listed by Cheon [12] for programming languages, C++ [17], [30], [34], .NET [4], Python [29], Smalltalk [11] and Java [6], [21], [22], [14]. A comprehensive report on the history of runtime assertion checking can be found in Clarke and Rosenblum's IMPACT report [13].…”
Section: Related Workmentioning
confidence: 99%
“…Besides the ones mentioned above there are numerous other runtime assertion checking facilities that have been developed. Here are some that are listed by Cheon [12] for programming languages, C++ [17], [30], [34], .NET [4], Python [29], Smalltalk [11] and Java [6], [21], [22], [14]. A comprehensive report on the history of runtime assertion checking can be found in Clarke and Rosenblum's IMPACT report [13].…”
Section: Related Workmentioning
confidence: 99%
“…For example, we reviewed five DBC tools for C#, including Spec# [5], the tool by Köhne et al [16], XC# [24], Contract Wizard [3], and Contract Sharp [14] and found that they can be put into the five categories of Fig. 1 XC# supports the specification of preconditions and postconditions with RequiresAttribute and EnsuresAttribute.…”
Section: Related Workmentioning
confidence: 99%
“…15 It works by reading in a .NET assembly and listing all the types and methods from the assembly and allows for preconditions, postconditions and invariant checks to be entered as Eiffel expressions. These preconditions, postconditions and invariants are added to the Eiffel proxy class using Eiffel's language constructs.…”
Section: Summary Of Related Workmentioning
confidence: 99%